Meningkatkan Kemampuan Bahasa Indonesia Menggunakan Metode Scaffolding Melalui Media Gambar pada Kelompok A - Citra Yudistira; Feti Wijayanti (Universitas Trunojoyo Madura, 2016)
Development of language skills for early childhood is very important aim to enable children to communicate orally with the environment. The problems in this research are 1) How the application of scaffolding strategy through dialogue activities can improve the ability of Indonesian language through the media of drawing on students of group A in Tk Anugerah Kamal ?; 2) Is there any improvement of Indonesian language through the media of image in group A students at Tk Anugerah Kamal, after learning by using scaffolding strategy as a learning method through dialogue activity with image media ?. Type of research used is Classroom Action Research. The result of research stated that there is an improvement on the students' Indonesian language skill by using scaffolding method through the image media in group a student in kindergarten of Kamal Anugerah. It can be seen from the data of cycle-to-cycle score which shows the criteria of the improvement of Indonesian language ability in the students are: 1) Before the cycle, the students who get the score 2 as many as 6 children reached 27.3%, while the score of 3 as many as 15 children reached 68, 2%; 2) In cycle I, students who can score 4 reach 31.8% (for 6 children) and score 5 reach 27.3% (for 7 children); 3) In cycle II, students who got score 4 reached 40.9% (for 9 children) and score 5 reached 50% (for 11 children)